2011
DOI: 10.1002/sia.3513
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of Nb materials for SRF cavities

Abstract: Superconducting Radio Frequency (SRF) cavities provide enhanced efficiency and reduced energy consumption in present-day particle accelerators. Niobium is the material of choice for SRF cavities due to its high critical temperature and critical magnetic field. In order to understand why certain treatments, especially a low temperature bake, improve performance, it is important to study Nb surface characteristics and identify elemental contaminants which may affect the performance of the cavity. [1] Initial stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The implanted samples showed typical Gaussian shaped curves for all four elements in silicon, but only for C, N, and O in niobium. The D profile in niobium showed no implant peak, indicating that the D is very mobile and can diffuse through the metal either without assistance or with the influence of the charged analysis beam [49]. Analysis of the SIMS standard provided relative sensitivity factors from which quantitative results for C, O, and N could be obtained.…”
Section: Sims Analysis Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The implanted samples showed typical Gaussian shaped curves for all four elements in silicon, but only for C, N, and O in niobium. The D profile in niobium showed no implant peak, indicating that the D is very mobile and can diffuse through the metal either without assistance or with the influence of the charged analysis beam [49]. Analysis of the SIMS standard provided relative sensitivity factors from which quantitative results for C, O, and N could be obtained.…”
Section: Sims Analysis Methodsmentioning
confidence: 97%
“…Depth resolution for SIMS is typically improved by analysis at lower impact energy. Some of the initial analyses were made at Cs þ impact energy of 6 keV and show improved depth resolution at the surface compared with 14.5 keV bombardment [49]. This condition was primarily used as a check for N at the surface after the initial nitrogen exposure experiments.…”
Section: Sims Analysis Methodsmentioning
confidence: 99%
“…The analysis chamber was also kept under UHV conditions ($ 10 À10 Torr) to minimize contamination. Ion implantation was used to obtain standards of C, O, and N in Nb [18]. Since N does not have a significant negative secondary ion yield in SIMS, NbN À ions were used to monitor the N À signal.…”
Section: A Sims Analysismentioning
confidence: 99%
“…Quantification of O was established by ion-implanted standards from an earlier study. [1] Analyses for C and N showed no significant contribution in the samples. Analysis for H is complicated by the extremely high mobility of this element in Nb.…”
Section: Resultsmentioning
confidence: 96%
“…The results were quantified with the use of ion-implanted standards. [1,2] Performance of SRF Nb was shown to improve after a lowtemperature bake, and it was found that reduction of H plays an important role. No significant changes were observed for C and N. Oxygen was associated primarily with the 5-7 nm surface oxide, and only minor differences in the bulk oxygen concentration were noted.…”
Section: Introductionmentioning
confidence: 98%